Buffer Zone Degradation and Plankton Dynamics in Northern and Northeastern Parts of Lake Tana, Ethiopia: Implications for a Tropical Highland Lake Ecosystem - Degsera Aemro; Ayenew Masresha; Ayalew Wondie; Marishet Teshome; Dagnew Mequanent (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT Lake Tana, a UNESCO World Biosphere Reserve Lake. The lake contains 50% of Ethiopia's freshwater and fertile land, which favoured urbanization, agriculture and irrigation, impacting its ecosystem. Understanding the effects of buffer zone degradation on plankton and water quality was vital for sustainable resource utilization. Therefore, data collection was conducted from December 2020 to May 2021 in the buffered zone, two non‐buffered zones, and the pelagic area of the northern and northeastern parts of Lake Tana twice a month. The study highlighted significant spatial variability in water quality and plankton composition, emphasizing the critical role of buffer zones for maintaining Lake Tana's health. Water temperature, dissolved oxygen (DO), Secchi depth, total dissolved solids (TDS) and nutrient concentrations varied significantly across sites, with degraded buffer zones (Seraba and Kirrigna) showing poorer conditions compared to buffered (Debresina) and pelagic areas. Phytoplankton communities were dominated by Chlorophyceae (46.15%), followed by Bacillariophyceae (30.77%), Cyanophyceae (19.23%) and Euglenophyceae (3.85%). Microcystis was the most abundant genus across all sites but was less prevalent in the buffer zone area. Zooplankton composition also varied significantly, with Rotifera dominating over Copepod and Cladocera. Chlorophyll‐a (Chl‐a) concentrations, an indicator of phytoplankton biomass, were highest in buffered and pelagic areas, showing positive correlations with DO and negative correlations with temperature and turbidity. Human activities significantly impacted water quality and plankton diversity, as evidenced by strong correlations with the human disruption assessment (HDA) score. Significant differences were observed between sites for most parameters, except temperature, oxygen content and zooplankton diversity. Mean Chl‐a concentrations were higher in pelagic (2.64 µg/L) and Debresina (5.3 µg/L) compared to Seraba (2.34 µg/L) and Kirrigna (2.48 µg/L). These findings emphasize the urgent need for policymakers and stakeholders to protect and restore Lake Tana's buffer zones.